Beweise von Sätzen mit Hilfe der Modelle der hyperbolischen Geometrie - Horváth, Jenő (Teaching Mathematics and Computer Science, 2003)
We give simple proofs for some problems of elemental hyperbolic geometry using the Poincare's half-sphere model. Our method is that a point of a figure is transformed to a special point of the model.